PENINGKATAN KAPASITAS ADMINISTRASI POKDAKAN MENUJU KEMANDIRIAN AKSES PROGRAM BANTUAN PEMERINTAH DI KELURAHAN TALIPPUKI, MAMASA - Irmawati Irmawati; Irmayanti Irmayanti; Sakinah Saharuna; Ratih Purwati Tahir (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Limited access to information and low bureaucratic administrative skills represent major structural barriers for communities in remote rural areas to access government assistance programs. This community service activity aims to provide organizational governance mentoring for fishery groups and enhance administrative literacy capacity through hands-on training in independently drafting fish seed assistance proposals. The activity was conducted from January 20 to February 03, 2026, in Kampuang Neighborhood, Talippuki Village, Mambi District, Mamasa Regency. The method applied was a participatory approach (Participatory Rural Appraisal) through stages of socialization, group institutionalization mentoring, hands-on computer-based training, and interactive discussions. The results demonstrated significant improvements in both institutional aspects and local human resource capacity. This program successfully initiated and established an official Fish Cultivator Group (Pokdakan) named